Determining baselines and trends of Eastern chimpanzees and forest elephants in a Central African protected area after civil strife - Funk, S.M.; Nkono, J.; Lushimba, A.; Fa, J.E.; Williams, D. (Elsevier, 2022)
Protected areas are crucial to safeguard Sub-Saharan Africa’s extraordinary and abundant megafauna. In many of these areas, instability has derailed conservation efforts and impeded adequate wildlife monitoring. Discovered in 2004, Eastern chimpanzees are found in the Central Uele Basin in northern Democratic Republic of Congo (DRC) within the Bili-Uéré Protected Areas Complex (BUPAC), the largest contiguous protected area in the country. BUPAC is threatened by habitat destruction, mining, wild meat trade, and insecurity. BUPAC chimpanzees are part of the largest remaining continuous population of the species in Africa; they are also being behaviourally unique. Forest elephants were frequent in the 1960′s in the BUPAC but have declined significantly up to 2004–2007. We used line transects to estimate Eastern chimpanzee and forest elephant density in the BUPAC core area in 2016 and 2019 and compared these with the 2004–2007 surveys. A total of 37 and 137 two km long line transects were systematically placed in 5,841 km2 and 6,176 km2 survey areas in 2016 and 2019, respectively. We found that chimpanzee density did not change during the two survey periods but indicators for forest elephant density decreased eight-fold. Human activities were detected mainly along the core area periphery in both survey years, where they overlapped with centres of animal activity. The stable high density of chimpanzees is a positive outcome for the core BUPAC. However, despite being a conservation priority area that has received relatively intensified protection, declining forest elephant numbers are likely to reflect the high number of human conflict hotspots in vicinity as well as the increasing human population density around the core area. We propose by elevating the core area to National Park whilst strengthening on the ground enforcement and management structures as well as legal measures against poaching might ensure the long-term survival of such an important area in Africa.